Transient acquired amegakaryocytic thrombocytopenia associated with Pediatric Hodgkin Lymphoma: A case report - Fatima Meraj; Hafsa Muhammad Hanif; Muhammad Rahil Khan; Neelum Mansoor (Elsevier, 2021)
Acquired amegakaryocytic thrombocytopenia (AAMT) is a rare disorder characterized by severe thrombocytopenia resulting from a marked reduction or absence of bone marrow megakaryocytes, and preserved hematopoiesis in other cellular lineages. We report a unique case of AAMT associated with Hodgkin Lymphoma, with spontaneous recovery following multiple cycles of combination chemotherapy. Our case provides evidence that AAMT associated with an underlying lymphoproliferative disorder may spontaneously recover following chemotherapy for the primary disease, and conservative management of thrombocytopenia could be considered in this setting.